Introduction to machine learning and its application in chemistry - Fechner, Nikolas (Henry Stewart Talks, 2011)
Data representation in machine learning, Learning success models, Overfitting, Complexity control by design, Supervised & Unsupervised machine learning, Quantitative Structure-Activity Relationship (QSAR), Molecular descriptors, A descriptor based QSAR model, Choosing a learning objective, Machine learning evaluation, Clustering, Distribution estimation, Virtual screening (VS), VS performance estimation